Exploring Digital Marketing Strategies during the New Normal Era in Enhancing the Use of Digital Payment - Gede Sri Darma; I Putu Teddy Noviana (Jurnal Mantik, 2020)
The New Life Order greatly affects the country's economy. COVID-19 has had a huge impact on tourism in Bali. People who work in the tourism sector are mostly laid off because the level of the visit is decreasing every month. The people who were sent home finally started to open new businesses to support the family economy. Currently, people still take advantage of conventional marketing in marketing their products. In the New Normal Era, people as traders should take advantage of technology in terms of product marketing. In addition, in terms of payment, the public should have used Digital Payment to reduce cash reduction because cash is one of the media for viruses to be intermediated. Bank Indonesia as an institution that regulates digital finance through policies should have the right strategy in helping MSMEs market their products through Digital Marketing so as to increase the use of Digital Payment and support the acceleration of a cashless society in Indonesia. This research used a qualitative method in the form of a case study conducted at one of the MSMEs assisted by Bank Indonesia. So that it is known that Bank Indonesia's strategy in developing fostered MSMEs to survive the midst of the COVID-19 pandemic by utilizing Digital Marketing while simultaneously increasing the use of Digital Payment to accelerate digital finance in Indonesia. The strategy used by Bank Indonesia also needs to be implemented by other institutions that have assisted MSMEs.